Analisis Penjualan Produk Air Minum Dalam Kemasan Menggunakan Metode Least Square Dan Angka Indeks Pada Pt. Panen Embun Kemakmuran Tahun 2022 - Ines Saraswati Machfiroh; Gati Anjaswari; Cahaya Ayu Ramadhan (P3M Politeknik Negeri Banjarmasin, 2023)
Sales are the main part of a company's operations, but sales that occur can increase or decrease sales (fluctuation) and cause sales losses. Sales losses can be anticipated by conducting sales analysis using Least Square, an index number that describes the factors that influence sales. The results of this research aim to predict sales of all products sold in 2022 by calculating Least Square and calculating index numbers to determine the increase or decrease in the percentage of sales levels from January to March 2022. The research found that (1) the percentage of sales levels in January until March 2022 there was an increase in sales of 1,323,850 units compared to sales in 2021, namely 550,058 units; and (2) the percentage of sales in January experienced an increase in sales of 19%, in February there was an increase in sales of 49% and in March there was a decrease in sales of -1%.